Circ_0124346 facilitates cell proliferation of pancreatic adenocarcinoma cells by regulating lipid metabolism via miR-223-3p/ACSL3 axis - Meng-lu Shu; Wan-ting Yang; Hui-min Li; Cui-juan Qian; Xiao-sheng Teng; Jun Yao (Discover Oncology)
Abstract Background Both lipid metabolism and cyclic RNAs (circRNAs) have been found to be involved in pancreatic adenocarcinoma (PAAD) progression, but the relationship between lipid metabolism and circRNAs remains unclear. Methods The expression levels of miR-223-3p, circ_0124346, and acyl-CoA synthetase long chain family member 3 (ACSL3) were determined through qRT-PCR and Western blot analysis. Cell proliferation was evaluated using the CCK-8 and EdU incorporation assays. Cholesterol (CH) and triglyceride (TG) levels were quantified using relevant kits. The relationships between miR-223-3p and circ_0124346 or ACSL3 mRNA were examined by bioinformatics analysis, luciferase reporter, RNA-RNA pull-down, and RIP assays. Results We observed a significant elevation in circ_0124346 expression in both pancreatic adenocarcinoma (PAAD) tissues and cell lines, and its expression level was shown to be correlated with tumor size. Circ_0124346 stimulated cell proliferation and facilitated lipid synthesis in PAAD cells. Additionally, we found that circ_0124346 functioned as a sponge for miR-223-3p, preventing miR-223-3p’s binding to the 3'-UTR of ACSL3 mRNA, which subsequently led to an elevation in ACSL3 expression and promoted lipid synthesis. Accordingly, circ_0124346 knockdown resulted in a significant decrease in lipid synthesis and cell proliferation in PAAD cells, with partial reversal of these effects achieved via inhibiting miR-223-3p or overexpressing ACSL3. Conclusion Our study demonstrated that circ_0124346 regulates lipid metabolism in PAAD cells via the miR-223-3p/ACSL3 axis, suggesting that targeting circ_0124346 may serve as a potential strategy for treating PAAD and assisting in its diagnosis.